Alterations in nociception and body temperature after intracisternal administration of neurotensin, beta-endorphin, other endogenous peptides, and morphine. - Nemeroff, C B (1979)
The antinociceptive and hypothermic effects of intracisternal administration of 11 endogenous neuropeptides and morphine were evaluated in mice. Of the substances tested, only neurotensin (NT) and beta-endorphin exerted significant antinociceptive and hypothermic effects; NT was the most potent in inducing hypothermia whereas beta-endorphin was the most potent antinociceptive agent via this route of administration. Both NT, and beta-endorphin were, on a molar basis, considerably more potent antinociceptive agents than morphine, [Met]enkephalin, or [Leu]enkephalin. NT-induced analgesia and hypothermia both were significantly dose-dependent. Substance P was found to produce significant hyperalgesia and hyperthermia. Bombesin produced a significant hypothermic effect, whereas somatostatin and luteinizing hormone-releasing hormone (luliberin) produced hyperthermia. None of the other peptides studies [bradykinin, thyrotropin-releasing factor (thyroliberin), melanocyte-stimulating hormone release-inhibiting factor (melanostatin), somatostatin, [Met]enkephalin, and [Leu]enkephalin] produced any significant alterations in colonic temperature or response to a noxious stimulus with the doses tested. These data demonstrate that NT and beta-endorphin, two endogenous brain peptides, are potent in inducing hypothermia and in producing an antinociceptive state.